Editorial - Mohanty, Bimal Prasanna (Journal of the Inland Fisheries Society of India, 2020)
It's my great pleasure to present you the first issue of the Vol. 51 of the JIFSI. This issue contains one opinion paper on non-plant based compounds to protect shrimp species against AHPND Vibrio parahaemolyticus by VikasKumar and Peter Bossire fromthe Ghent University, Belgium. A review article by Prakash Nautiyaland team present a picture on the coexistence of cold-water capture fishery in the Ganga up streams with hydropower plants.A research paper on nursing and rearing of mud eel Monopterus cuchia in Bangladesh have been contributed by Chakraborty and team. Big Data, Artificial Intelligence (AI) and internet of Things (IoT) are coming up in a big way both in biology and business. The article by A. K. Roy throws light on business analytics in fisheries and aquaculture and highlights its scope of application in this sector. I expect more papers on these aspects which can bring out succinctly the present day use and their future applications for enhancing productivity, livelihood improvement and other unconventional applications.Aftabuddin Md. and group report here the differential expression of TLRs in the catfish Heteropneustes fossilis in response to infection with the bacterial pathogen Aeromonas hydrophila. The paper by Chakraborty and co-workersthrows light on bio-activity guided isolation and structural characterisation of raphid crystals in ipomoea. The paper by Borah and his co-workers have compared the length-weight relationship and condition factor of geographicallyisolated hilsa populations. Sinhaand co-workershave presented a paper where focus is on empowering rural women through ornamental fish farming.In fact, 'ornamental fish farming' has a huge scope in the country, especially in theeastern and north-eastern states and this sector can provide employment to rural youth and women and can hugely improve their livelihood and can make the country (eastern India) the 'global ornamental fish hub' if nurtured, guidedand funded in the right way in public-private partnership (PPP)-mode by the appropriate agencies.